Strategic Utilization of Arabic Language Competencies of BSA Students for The Development of Tourism in Central Aceh - Sumardi; Aiyub Berdan; Rasyad; Chairunnisa Ahsana Amalan Shalihah; Fajri, Akmal; Irwan mus; Achmad Yani (Jurnal Adabiya, 2026)
This study aims to identify and analyze strategies for utilizing the Arabic language skills of students from the Arabic Language and Literature Study Program (BSA) in supporting the development of tourism in Central Aceh. The background of this research is rooted in the need to strengthen the competitiveness of the regional tourism sector based on Islamic values and local culture, while at the same time optimizing the linguistic potential of BSA students as a strategic human resource asset. This research employs a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and content analysis of digital publications produced by students and shared on the social media platforms of the BSA Department at UIN Ar-Raniry Banda Aceh. The findings indicate that Arabic language skills can be utilized in two main areas: digital marketing to attract tourists from Middle Eastern countries, and the development of educational tourism through the “Language Village” concept. Institutional collaboration between the BSA Study Program and the Central Aceh Tourism Office has also proven to create opportunities for sustainable synergy in training programs, cultural promotion, and applied research. This study concludes that Arabic is not only an academic tool, but also holds significant economic and cultural value for the development of local tourism. Abstrak Penelitian ini menganalisis model strategis pemanfaatan kompetensi bahasa Arab mahasiswa Program Studi Bahasa dan Sastra Arab (BSA) untuk mendukung pengembangan pariwisata di Aceh Tengah. Dengan menggunakan desain kualitatif deskriptif dan pendekatan studi kasus, data dikumpulkan melalui wawancara, observasi, serta analisis konten terhadap publikasi digital mahasiswa yang disebarluaskan melalui platform media sosial resmi Jurusan BSA UIN Ar-Raniry Banda Aceh. Hasil penelitian menunjukkan dua domain strategis utama, yaitu: (1) pemasaran digital yang menyasar wisatawan dari negara-negara Timur Tengah dan (2) pengembangan wisata edukasi melalui model “Kampung Bahasa”. Selain itu, kolaborasi kelembagaan antara Program Studi BSA dan Dinas Pariwisata Aceh Tengah terbukti mendorong terciptanya sinergi berkelanjutan dalam program pelatihan, promosi budaya, dan penelitian terapan. Secara teoretis, penelitian ini berkontribusi dengan memperluas kajian pendidikan bahasa Arab ke dalam kerangka pengembangan sosial-ekonomi dan budaya, serta secara praktis menawarkan model strategis yang aplikatif bagi perumusan kebijakan pariwisata daerah. Kebaruan penelitian ini terletak pada pengajuan model integratif yang secara sistematis mengaitkan kompetensi bahasa Arab mahasiswa dengan strategi pengembangan pariwisata dalam konteks budaya Islam lokal.